Radioweb PUCPR articulada pelas redes sociais: uma experiência inovadora no ensino superior - Cunha, Edjane Madza de Almeida (2013)
Quick changes have been occurring in the society lately. The technology has always been present in our lives and, today, we are more and more connected to networks, which contribute to extinguish the barriers and geographic distances. Each day we try to interact with other people, other cultures and, with only a click we are able to go round the world with the help of technology. To keep up with these changes of the society, in Education we have sought solutions to adjust new forms of teaching/learning to these new paradigms. The ICTs Information and Communication Technologies are an alternative to innovation in the process to acquire knowledge. In face of this reality, this research aims at identifying the contribution of the webradio use in the teaching learning process to promote interaction and participation among students of higher education. This research is a case study which was carried out in the discipline personnel management , with the students of the 5th period from the administration course of PUCPR Pontifical Catholic University of Paraná , with the production of the webradio series called Interaction series personnel management. The series were composed by 32 programs about innovation in the area of knowledge of personnel management, which were produced and presented by 147 students of the discipline. These series were based on Vygotsky theory about the learning process and development and also on the theory of Bakhtin about interaction. They supplied subsides that prove the hypothesis that the webradio articulated through social networks, fosters interaction enabling teaching/learning, besides contributing to the development of the skills and abilities required to perform the function of future administrators